2013
DOI: 10.1051/eas/1363003
|View full text |Cite
|
Sign up to set email alerts
|

CEMP-s and CEMP-s/r stars: last update

Abstract: Abstract. We provide an updated discussion of the sample of CEMP-s and CEMP-s/r stars collected from the literature. Observations are compared with the theoretical nucleosynthesis models of asymptotic giant branch (AGB) stars presented by Bisterzo et al. (2010Bisterzo et al. ( , 2011Bisterzo et al. ( , 2012, in the light of the most recent spectroscopic results.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
169
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(185 citation statements)
references
References 59 publications
16
169
0
Order By: Relevance
“…The [Pb/Ba] ratio varies by almost an order of magnitude, with the highest value (1.16) achieved for the −2m profile and the lowest (0.37) with the m 1/3 profile. This makes variations in the mixing profile at low metallicity one of the possible factors that could contribute to explaining the variations in [Pb/Ba] (within a similar range as found here) observed in carbonenhanced metal-poor (CEMP) stars with enhancements in the s-process elements (Van Eck et al 2003;Bisterzo et al 2010Bisterzo et al , 2011Bisterzo et al , 2012Lugaro et al 2012).…”
Section: Discussionsupporting
confidence: 80%
“…The [Pb/Ba] ratio varies by almost an order of magnitude, with the highest value (1.16) achieved for the −2m profile and the lowest (0.37) with the m 1/3 profile. This makes variations in the mixing profile at low metallicity one of the possible factors that could contribute to explaining the variations in [Pb/Ba] (within a similar range as found here) observed in carbonenhanced metal-poor (CEMP) stars with enhancements in the s-process elements (Van Eck et al 2003;Bisterzo et al 2010Bisterzo et al , 2011Bisterzo et al , 2012Lugaro et al 2012).…”
Section: Discussionsupporting
confidence: 80%
“…This is detectable in the isotopic abundance ratios of C and N, where low 12 C/ 13 C and [C/N] ratios indicate strong internal mixing with CN-cycled material (Spite et al 2005). For 13 of our programme CEMP stars we find ratios that cover 3 < 12 C/ 13 C < 50, where the higher end of this range is in good agreement with Bisterzo et al (2011Bisterzo et al ( , 2012, who find that their AGB models without strong mixing do not result in the low, observed values (4 < 12 C/ 13 C < 10).…”
Section: Comparison To Galactic Chemical Evolution Modelssupporting
confidence: 87%
“…This follows from the results of Lucatello et al (2005) and Starkenburg et al (2014) on binarity and of Bisterzo et al (2011) on nucleosynthesis.…”
Section: High-carbon Bandmentioning
confidence: 74%
“…This last requirement is supported by the study of Bisterzo et al (2011), who have analysed a sample of 100 CEMP-s stars for which detailed chemical abundances are available (almost all the stars that appear in Fig. 6 are in their sample) and showed that the abundances of light elements (C, N, O, Na, Mg) and neutron capture elements can be reproduced assuming transfer from an AGB star in the mass range 1.3−2 M and logarithmic dilution factors in the range 0.0−2.5.…”
Section: High-carbon Bandmentioning
confidence: 82%